Assessment of the effects of integrated coastal zone management based on synthetic control method - Qing, Yiting; Nie, Xin; Wang, Han; Wei, Zhuxia; Pang, Hui (Frontiers in Marine Science, 2022)
As a policy tool to promote sustainable development of coastal zone cities, Integrated Coastal Zone Management (ICZM) was introduced to China for experimentation in the 1990s. Among them, the Xiamen government took ICZM as an opportunity to conduct a large number of policy pilots, making the evaluation of the policy effects worth studying. This paper takes Xiamen city as the research object based on 180,000 samples from 188 Chinese municipalities from 1980-2017. Based on the theoretical framework of the Social-Economic-Natural Complex Ecosystem (SENCE), we use the synthetic control method (SCM) to conduct its two rounds of policy pilots. The study found that the first round of experiments focused on environmental pollution prevention and control, and the economic development gap between Xiamen and similar coastal zone cities was narrowed despite the economic lag effect. Finally, based on robustness tests, policy recommendations are made for coastal zone cities.